URGENSI REGULASI DAN EDUKASI PRODUK HALAL BAGI KONSUMEN - Maulida, Rahmah (Justitia, 2013)
The regulation of Halal Food is the important thing in context of Muslim of Indonesia. But the lack of education and socialization of halal products in Ponorogo give a significant impact to ignorance of society to consume the halalness. Actually, the consumers really realize that goverment must take a guarantee of safety products, like food, meat, drink, and medicine. But, they give difference opinions about the best strategies of certification of halalness in Indonesia. This article aim to explore the urgencies of educating the halalness, to protect the consumersâ rights in their intake daily life.Kata kunci:Halal Product, Halal Campaign, LPPOM MUI.